Biosafety of GM Crops in Kenya, Uganda, and Tanzania: An Evolving Landscape of Regulatory Progress and Retreat - Chambers, Judith A. (Rowman & Littlefield Publishers, 2013)
This report outlines the status of biotechnology regulatory structures in Kenya, Tanzania, and Uganda, with a focus on regulation of genetically modified (GM) crops. Effective regulatory structures are important for the approval and use of agricultural technology. As technologies become more sophisticated, so too must regulatory structures and risk assessment frameworks. This paper provides a detailed analysis of the biotechnology regulatory structures in Kenya, Tanzania, and Uganda; outlines the current status of each country’s biotechnology regulatory structures; and evaluates to what extent the status of each of these countries’ regulatory structures permit and/or impede GM adoption. Finally, the paper examines potential areas for regulatory harmonization between these countries at a regional level.